The impact of dietary rationalization on rural residents’ health and happiness - Liu, Weijun; Zhang, Siyuan; Florkowski, Wojciech J. (Frontiers in Sustainable Food Systems, 2025)
IntroductionChina is facing a dual burden of malnutrition and overnutrition, and dietary rationalization (DR) is an important direction for the transformation of rural residents’ dietary habits. The effect of DR on happiness has not been sufficiently researched in existing literature. Verifying the impact of the DR on the happiness of rural residents and analyzing the mechanism of health is necessary.MethodsThis study is based on a mixed cross-sectional data of the 2020–2022 China Land Economic Survey, establish a measurement for the DR and use OLS regression, two-step regression to analyze the effect of DR on happiness and the mechanism of health. The Propensity Score Matching method and Instrumental Variables are used to test the robustness of the effect of DR on happiness. Bootstrap method is used to confirm the robustness of the mechanism of health.ResultsThe baseline regression show that rationalizing diet can enhance the happiness of rural residents. A two-step regression shows that health plays a positive mediating role in the impact of the DR on the happiness of rural residents. After robustness tests, the above conclusion still holds. Heterogeneity Analysis shows that rationalizing the intake of fruits and milk can increase the happiness of rural residents, excessive consumption of meat and aquatic products will make rural residents happier. In addition, the marginal effect of rationalizing diet on the happiness of older and less educated rural residents is stronger.DiscussionThis study suggests that dietary rationalization has a significant impact on the health and happiness, expanding the possible ways to improve the happiness of rural residents from a micro perspective and providing references for the formulation of relevant policies like specific directions for improving the food supply system and the popularization of dietary literacy. Next, it is necessary to expand the food type and take a tracking study.